2017
DOI: 10.1136/bmjquality.u206639.w6166
|View full text |Cite
|
Sign up to set email alerts
|

A multifaceted approach to improving the quality of ENT Emergency Clinic referrals

Abstract: It is imperative that primary care referrals are directed to the appropriate secondary care service. Patients presenting to a primary care physician with ENT conditions may require review in an Emergency Clinic. The latter clinics provide patients with rapid access to secondary care, for urgent, yet non-life-threatening conditions. In our department, we noticed that patients with conditions inappropriate to the capabilities of the Clinic were being booked in or reviewed too late; thus causing wasted journeys f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…This notion is further supported by a review about service improvement in healthcare organization commending leadership interchange among professionals of various levels [10]. It stands to reason that directing cases to the appropriate healthcare professionals, such as senior specialist registrars or specialist nurses, could optimise the clinical workflow, potentially reducing referral backlogs and facilitating increased patient bookings [9]. Furthermore, addressing inappropriate referrals is crucial in ensuring efficient patient care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion is further supported by a review about service improvement in healthcare organization commending leadership interchange among professionals of various levels [10]. It stands to reason that directing cases to the appropriate healthcare professionals, such as senior specialist registrars or specialist nurses, could optimise the clinical workflow, potentially reducing referral backlogs and facilitating increased patient bookings [9]. Furthermore, addressing inappropriate referrals is crucial in ensuring efficient patient care.…”
Section: Discussionmentioning
confidence: 99%
“…This surge in routine cases strains resources unnecessarily, potentially impeding the clinic's ability to allocate resources effectively and provide optimal care to individuals in urgent need. Hence, striking a delicate balance between managing urgent cases and appropriately addressing routine cases becomes imperative to ensure an efficient and effective healthcare delivery system within the clinic [9]. Our primary goal was to scrutinize and assess the cases referred to the clinic, aligning them with clinical priorities.…”
Section: Challenges and The Need For Balancementioning
confidence: 99%
“…The first step to improve communication is having a clear guideline on the content of communications; unfortunately, as manual processing is inaccurate, to prevent cases like those described in the literature, 14,78,79 templates should be used as they improve documentation 41 ; a second step is improving interoperability, which should be easier following an agreement on what information and what format to follow, and in this respect the use of the same medical codes to facilitate the information processing. A third step should be adapting the basic information shared to accommodate additional information required, like for example for heart failure services the weight of the patient at discharge, 64 but it should be reciprocated, so both parties share the latest information, update it and in consequence a coordinated care results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews on communication between primary and secondary care have shown issues such as general practitioners satisfaction, 75 secondary clinicians attitudes, 76 educational needs, 38,77 lack of standardisation, 75 benefits from information technology like templates, 77 information management 40 and timeliness. 76 Content has also been assessed, [75][76][77] but not been the focus as on this paper.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…In the UK, ENT casualty clinic is frequently led by senior house officers (SHOs), and thus, SHOs are often the responsible clinicians for assessing and listing patients for MUA. Likewise, the SHO may consent the patient for the procedure and should be aware of the relevant risks and adverse outcomes 6 7…”
Section: Discussionmentioning
confidence: 99%